An update on male hypogonadism therapy. (June 2014) - Surampudi, Prasanth; Swerdloff, Ronald S; Wang, Christina
<x xml:space="preserve">Abstract</x> Introduction: Men who have symptoms associated with persistently low serum total testosterone level should be assessed for testosterone replacement therapy. Areas covered: Acute and chronic illnesses are associated with low serum testosterone and these should be recognized and treated. Once the diagnosis of male hypogonadism is made, the benefits of testosterone treatment usually outweigh the risks. Without contraindications, the patient should be offered testosterone replacement therapy. The options of testosterone delivery systems (injections, transdermal patches/gels, buccal tablets, capsules and implants) have increased in the last decade. Testosterone improves symptoms and signs of hypogonadism such as sexual function and energy, increases bone density and lean mass and decreases visceral adiposity. In men who desire fertility and who have secondary hypogonadism, testosterone can be withdrawn and the patients can be placed on gonadotropins. New modified designer androgens and selective androgen receptor modulators have been in preclinical and clinical trials for some time. None of these have been assessed for the treatment of male hypogonadism. Expert opinion: Despite the lack of prospective long-term data from randomized, controlled clinical trials of testosterone treatment on prostate health and cardiovascular disease risk, the available evidence suggests that testosterone therapy should be offered to symptomatic hypogonadal men.